Evaluasi Pemajakan Terhadap Penyelenggara Sistem Elektronik Transaksi Digital yang Berasal dari Luar Negeri - Maya Mahatma Putri; Yulianti Abbas (Politeknik Ganesha Medan, 2023)
Cross-border trade brings new digital taxation issues in Indonesia. There are several tax treatment for foreign electronic sistem operators for trading through the electronic sistem in Indonesia. This study aims to evaluate the implementation of taxation of foreign electronic sistem operators based on the